(untitled) (International Journal of Engineering and Computer Science, 2018)
Capture the data flowing from client application to the server in a network as pcap files. And then, analyze them to detect if they contain sql injection type string patterns. SQL injection is an attack in which malignant code is inserted into strings that are eventually passed as an instance of sql server